2018
DOI: 10.4314/ijbcs.v11i5.24
|View full text |Cite
|
Sign up to set email alerts
|

Variabilité climatique et production maraîchère dans la plaine inondable d’Ahomey-Gblon au Bénin

Abstract: RESUMELe maraîchage pratiqué dans les plaines inondables fait partie des activités qui assurent la diversification des habitudes alimentaires dans le but de contribuer à la sécurité alimentaire et à la réduction de la pauvreté. Cependant, dans les pays au Sud du Sahara, la variabilité climatique représente une grande menace pour la croissance et le développement durable. La présente étude se propose d'évaluer les effets de la variabilité climatique sur la production maraîchère dans la plaine inondable d'Ahomey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
1
0
4
Order By: Relevance
“…Similar results were observed by several authors who studied changes in Benin's climate (ATIDEGLA et al, 2017;BOKO et al, 2012;DJOHY et al, 2015) and found that Benin had a longer period of water deficit than periods of water surplus in the different seasons.…”
Section: Seasonal Variation In Rainfall and Evapotranspiration In Beninsupporting
confidence: 88%
“…Similar results were observed by several authors who studied changes in Benin's climate (ATIDEGLA et al, 2017;BOKO et al, 2012;DJOHY et al, 2015) and found that Benin had a longer period of water deficit than periods of water surplus in the different seasons.…”
Section: Seasonal Variation In Rainfall and Evapotranspiration In Beninsupporting
confidence: 88%
“…Par ailleurs, plusieurs études ont porté sur les conséquences des changements climatiques sur la production maraîchère (Atidegla et al, 2017), la productivité (Tchabi et al, 2012), les produits chimiques (Agueh et al, 2015 ;Chouti et al, 2018) et la filière maraîchère (Agossou et al 2001). De nombreuses potentialités (utilisation des semences à cycle court, agriculture de contre saison, etc.)…”
Section: Introductionunclassified
“…Tomato (Solanum lycopersicum L.) is a herbaceous, perennial, annual, branching-stem plant cultivated worldwide for its fruits which are eaten fresh or processed. In the new climatic context with its corollary of reduced rainfall [1], abiotic diseases are becoming more and more restrictive. Among these diseases, the blossom end rot causes extensive damage, contributing to over 50 % of production loss [2].…”
Section: Introductionmentioning
confidence: 99%